Effect of Designed Ureteral Stent Instructions on Patient Recovery - Safaa M. Hamed; Rasha F. M. Gaballah (Evidence-Based Nursing Research)
Contents: Ureteral stent placement is performed in up to eighty percent of patients following ureteroscopy. It associated with significant morbidity, resulting in a reduction in general health function in another eighty percent of patients.